French Aedes albopictus are able to transmit yellow fever virus - Amraoui, Fadila (Euro Surveill, 2016)
We assessed the ability of a French population of Aedes albopictus to transmit yellow fever virus (YFV). Batches of 30 to 40 female mosquitoes were analysed at 7, 14 and 21 days post-exposure (dpe). Bodies, heads and saliva were screened for YFV. Infectious viral particles were detected in bodies and heads at 7, 14 and 21 dpe whereas the virus was found in saliva only from 14 dpe. Our results showed that Ae. albopictus can potentially transmit YFV.